THE EFFECT OF TYPES FOOD AND THEIR DIFFERENT COMBINATION ON GROWTH AND SURVIVAL RATE OF MUTIARA CATFISH LARVAE (Clarias gariepinus Burchell, 1822) - Pandiangan, Tito Fresly; Sukendi, Sukendi; Nuraini, Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The research was conducted for 6 weeks from October 22nd until December 2nd2018 at fish breeding and breeding laboratory (PPI) Department of Aquaculture, Faculty of Fisheries and Marine, University of Riau, Pekanbaru. The aim of this research was to investigated the effect of types and their different combination on the growth and survival rate of mutiara catfish larvae (Clarias gariepinus Burchell, 1822). The method used in this study is the experimental method that uses one-factor Completely Randomized Design (CRD) consisting of six treatments with three replications. The treatment applied in this study is A6 (Artemia sp. 6 weeks), PP6 (Paste feed 6 weeks), T6 (Tubifex sp. 6 weeks), A3T3 (Artemia sp. 3 weeks, Tubifex sp. 3 weeks), PP3T3 (Paste feed 3 weeks, Tubifex sp. 3 weeks), and A2PP2T2 (Artemia sp. 2 weeks, Paste feed 2 weeks, Tubifex sp. 2 weeks). The results showed that the best treatment of types and their different foods combination was found in T6 treatment (Tubifex sp. 6 weeks) produces absolute weight growth of 2,2171 grams, growth of absolute length of 6,80 cm, specific growth rate of 16,16%, while the best survival rate found in the A3T3 treatment (Artemia sp. 3 weeks, Tubifex sp. 3 weeks) is 84,44%. Water quality during the study was temperature ranging from 26-280C, pH ranged from 6-7 and DO was 4,0-6,0. Keywords : Types food, Artemia sp., Pasta Food, Tubifex sp., Larvae of mutiara catfish (Clarais gariepinus Burchell, 1822)